Pemanfaatan Sampah Organik Dijadikan Kompos - Fairuz A, Ilham; Rosyidah A, Ummi; Novrianti, Fadhilah; Ningrum, Dian Eka Aprilia Fitria (Experiment: Journal of Science Education, 2023)
Waste is a fundamental problem in every region. Starting from the inappropriate construction of waste, it is hoped that the community's role in overcoming this fundamental problem needs to be aware of the importance of separating organic and non-organic waste. So that the solution to the waste problem can be resolved with high awareness by the community itself, one of the efforts, contributions and concern for waste is realized by establishing a waste bank. The purpose of this observation is to find out more about what Rumah PKD Jatimulyo does in managing organic waste after entering Rumah PKD Jatimulyo. The city of Malang knows handling strategies in managing waste starting from the community's own awareness, such as differentiating waste when they want to dispose of it by making several trash cans to differentiate organic waste from non-organic waste. The research method used is qualitative. This qualitative method was chosen because it aims to understand what phenomena occur after the waste enters the Jatimulyo PKD House from an in-depth and contextual point of view. This qualitative method includes descriptive data collection, such as observation, interviews, documentation. The results of the research can be concluded that Rumah PKD Jatimulyo contributes to organic waste management in Jatimulyo Village, Lowokwaru District, Malang City. Rumah PKD Jatimulyo's contribution in managing organic waste is a form of increasing the surrounding environmental resources. This can be felt by local communities who may need alternative fertilizers to grow plants at home or in community plantations.